Ceramic bone graft substitute (Mg-HA) in spinal fusion: A prospective pilot study - Griffoni, Cristiana; Tedesco, Giuseppe; Canella, Valentina; Nataloni, Angelo; Zerbi, Alberto; Tosini, Giovanni; Gasbarrini, Alessandro; Barbanti-Brodano, Giovanni (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Iliac crest bone graft (ICBG) is considered the gold standard for spine surgical procedures to achieve a successful fusion due to its known osteoinductive and osteoconductive properties. However, complications related to harvesting procedure and donor site morbidity have been largely reported in literature, favouring the development of a wide range of alternative products to be used as bone graft extenders or substitutes for spine fusion. Among all, ceramic-based biomaterials have been widely studied and employed in the last years as bone graft substitutes. Methods: We report here the results of a prospective pilot study aimed to evaluating the grade of ossification obtained by the use of an Mg-doped hydroxyapatite (HA) product to achieve postero-lateral fusion in degenerative spine diseases. Results: Results show a successful degree of fusion of about 62% at 12 months follow-up and an improvement of quality of life and health status following surgery, as evaluated by clinical scores (ODI, VAS and EQ-5L). No adverse events related to the material were reported. Conclusions: The present pilot study shows the effectiveness and the safety profile of a Mg-doped HA bone graft substitute used to achieve postero-lateral fusion in the treatment of degenerative spine diseases, laying down the basis for further, larger clinical investigations.